The Effectiveness of the Card-Based Make-A-Match Method in Teaching Fantasy Text Writing to Seventh-Grade Students - Amanda Ivani; M. Badrus Siroj (Raja Zulkarnain Education Foundation, 2026)
This study aims to analyze the effectiveness of the Make-A-Match learning model on the learning outcomes of seventh-grade students in fantasy text writing. The study was conducted at SMP Negeri 9 Semarang on November 1, 2025. This study used an experimental method with a pretest-posttest control group design. The subjects consisted of two classes: an experimental class and a control class, each with 32 students. Data collection was conducted through a fantasy story text writing test administered before and after the treatment. Data analysis included normality tests, homogeneity tests, independent sample t-tests, paired sample t-tests, and the N-Gain test to determine improvements in learning outcomes. The results showed that the data were normally distributed and homogeneous. The independent sample t-test showed a significant difference between the experimental and control classes with a significance value of 0.003 <0.05. Furthermore, the results of the paired sample t-test indicated a significant improvement in the experimental class after the treatment. The average post-test score for the experimental class was 94.38, higher than the 91.19 for the control class. The N-Gain test results showed that the experimental class achieved 72.02% improvement in learning outcomes, which is considered high, while the control class achieved 63.12% improvement, which is considered moderate. Therefore, it can be concluded that the Make a Match learning model is effective in improving the learning outcomes of seventh-grade students in fantasy text writing at SMP Negeri 9 Semarang.